The governor is a woman who lives with the pain of the people - Dilafruz Hasanova (Zien Journals, 2021)
In this article we talk about woman who cares about people and also the fact that today the chairman of the Senate of the Oliy Majlis of the Republic of Uzbekistan is a woman, women make up 35% of the Legislative Chamber of the Oliy Majlis of the Republic of Uzbekistan, 8 courageous women in district and city khokimiyats.
Keywords: Pain; people; respect; women